Validation of the swimming competence questionnaire for children. Issue 14 (17th July 2020) - Chan, Derwin K. C.; Lee, Alfred Sing Yeung; Macfarlane, Duncan J.; Hagger, Martin S.; Hamilton, Kyra
ABSTRACT: Two studies were employed to test the reliability and validity of the Swimming Competence Questionnaire (SCQ) among primary school children. Study 1 was a cross-sectional survey in 4959 primary school children. Study 2 was a pre-post-test quasi-experiment among 1609 primary school children who underwent a 20-lesson learn-to-swim programme. In Study 1, exploratory structural equation modelling revealed excellent goodness-of-fit and scale reliability for a two-factor model comprising distance and skill factors, which supported the construct and convergent validity. SCQ scores were significantly and positively correlated with swimming outcomes (i.e., self-efficacy, intention, swimming frequency), which supported SCQ's concurrent and criterion validity. Average variance extracted for the SCQ factors exceeded cut-off criteria supporting discriminant validity. In Study 2, pre-test SCQ scores correlated significantly and positively with the SCQ scores, self-efficacy, intention, and swimming frequency at post-test, which supported SCQ's test-retest reliability and predictive validity. Positive intraclass correlation between SCQ scores and coach ratings at post-test provided evidence for SCQ's inter-rater reliability. SCQ scores significantly improved at post-test, which supported SCQ's ecological validity. In conclusion, findings indicate that the SCQ is a valid and reliable measure to assess primary school children's swimming competence, in terms of swimming distance and basic water survival skills.